Projeto Político Pedagógico em Ação : discutindo a emancipação de base freiriana - a voz de educandos do Colégio Municipal Pelotense - Barz, Carlos Alberto (2010)
The construction of a humanized world demands the implementation of critical and educational processes capable to transform. In this sense, this work aimed to analyze the development of the emancipation concept proposed by the pedagogic political project of the Pelotense Municipal School, taking into account that this is taken from Paulo Freire's thought. This way, the central objective of this research looked for answering in what measure the students of this school manifest some indication of a coherent positioning of emancipation with the political-pedagogic proposal of Freire. Starting from the speech of the pedagogic coordination of the researched school it was noticed that the emancipation concept is interpreted as a political conquest executed from the political-social emersion, looking for each subject's formation gone back to the compromising with a society project in the direction of the universal objectives. The research demonstrated that there are approaches of the emancipation concept thought by the Pelotense Municipal School and the be-more freiriana category . As methodological procedure, the investigation used the resource of the established dialogue starting from the meeting between the thought of Freire and the subjects of the research (students of the third year of the high school). In the investigative way the study intended to unfold the freiriano s be-more, from where were extracted the categories: autonomy, dialogue, understanding and the ethics, that were used to theorize the exhibition of the subjects of the research mediated by the problem-solving of the emerging themes in the socioeconomic reality of the students